2017
DOI: 10.4103/2230-8210.196009
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic dietary advice for diabetes during Navratris

Abstract: Navratri is one of the most common religious fasts observed among Hindus. A large number of people with diabetes follow Navratris fast irrespective of its health implications, often without proper education and medical advice. The quest for the scientific research on dietary advices for Hindu fasts including Navratris shows paucity of literature comparative to the dietary advices advocated during Ramadan. The eating and physical activity patterns during different fasts vary a lot depending up on social and cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Regarding environmental barriers (e.g. temptations during festivities and religious events), our findings are similar to those in other countries (Gallant et al, 2007; Gupta et al, 2017). Studies on Western and South Asian communities show that the consumption of sweet foods among PLwD is an issue (Lawton et al, 2008; Singh et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding environmental barriers (e.g. temptations during festivities and religious events), our findings are similar to those in other countries (Gallant et al, 2007; Gupta et al, 2017). Studies on Western and South Asian communities show that the consumption of sweet foods among PLwD is an issue (Lawton et al, 2008; Singh et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…The results also showcase that exploring ways to modify Pakistani cuisine to help PLwD resist food temptations is important. Research by Gupta et al (2017) has shown that modifications to celebratory meals during Navratri fasts for Hindu believers can be suggested to families and stakeholders without completely eliminating traditional foods. This is important because festive and religious meals hold significant cultural value and completely changing them can be challenging for individuals with dietary restrictions and their families.…”
Section: Discussionmentioning
confidence: 99%
“…People with diabetes are faced with multiple challenges related to diet, physical activity pattern, healthcareseeking behaviour and healthcare provision during such occasions. 5 Family or spousal compliance towards the glycaemic management of their affected relative is paramount. The patient can be supported through practices such as healthy eating, medical nutrition therapy, avoiding excessive outdoor meals and erratic meal patterns, selfcare practices, blood glucose monitoring, physical activity, medication administration, and management of acute complications may; all of which will enhance compliance for the effective management of diabetes during the cultural and religious occasions.…”
Section: Resultsmentioning
confidence: 99%
“…Optimal and appropriate diet, calorie restriction, physical activity and medication adherence are four key pillars of therapeutic lifestyle interventions in the management of diabetes. 4,5 In spite of awareness, poor compliance to therapeutic lifestyle interventions contributes to poor glycaemic control and increased end-organ damage resulting in poor quality of life in the long run. This perpetuates a viscous cycle of poor control and further complications, which at times, becomes difficult a difficult cycle for the patient to break.…”
mentioning
confidence: 99%
See 1 more Smart Citation